Prevalence and Regional Distribution of Lower Limb Amputations from 2006 to 2012 in Germany: A Population based Study. Issue 6 (December 2015) - Heyer, K.; Debus, E.S.; Mayerhoff, L.; Augustin, M.
Abstract : Objective/Background: International studies show conflicting results regarding the frequency of lower limb amputations over time. However, published data are often based on event related amputation frequencies per year, on hospital statistics or on regional surveys. Thus, they do not allow population based statements. The present study assesses the population based epidemiology of amputations in Germany. Methods: Secondary analyses of 80 German statutory health insurance companies with 4 million insurants nationwide in 2012 were performed. From 2006 to 2012, lower limb amputations were identified in the entire population and in persons with diabetes mellitus (DM) and arterial occlusive disease (AOD). Lower limb amputations and persons with DM and arterial occlusive diseases were extracted by specific operation procedure codes and International Classification of Diseases-10 codes. Descriptive standardized analyses by age, sex, and regional distribution were conducted. Results: The proportion of patients with at least one lower limb amputation in the entire population stayed constant over time at 0.04% (95% confidence interval [CI] 0.04–0.04). Extrapolated to the German population in 2012 there were 49, 150 cases and 32, 767 persons with amputations. In 2012, about 70% of amputations were minor (0.03% [95% CI 0.03–0.03]) versus major amputations (0.01% [95% CI 0.01–0.01]). Related to DM and AOD, there was a small decrease in the amputation rate per patient, even though the DM prevalence increased by 10.4%. Conclusion: The amputation rates per patient in Germany have remained stable in the overall population and show slight decline in patients with diabetes mellitus and with arterial occlusive disease between 2006 and 2012. In the future, intensified preventive measures are crucial to reduce the number of amputations of the lower extremities permanently.